Relationship Between Nutritional Status, Sodium, Potassium And Fiber With The Incidence Of Hypertension At The Cimaung Health Center, Bandung Regency - Lesipha Dwi Kumala; Asysyifa Riana; Iriyanti Harun (Saintify Publish, 2024)
Hypertension is a condition where blood pressure is more than 140/90 mmHg, which occurs because the heart pumps blood faster to fill oxygen and nutritional needs. This study aims to determine the relationship between nutritional status, sodium, potassium and fiber with the incidence of hypertension at the Cimaung Public Health Center, Bandung Regency. The research design used was case control. The sample consisted of 132 respondents consisting of 66 cases and 66 controls obtained by accidental sampling. Data collection on characteristics such as age, gender, level of education was obtained through interviews. Data on sodium, potassium and fiber intake was obtained through interviews using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) form and nutritional status data was obtained through direct measurements of body weight and height. Data analysis was carried out using the Chi Square test. Statistical test results of the relationship between nutritional status and hypertension (p-value = 0,456 (p>0.05)), sodium (p-value = 0,000 (p0.05)). The conclusion of this study is that there is a relationship between sodium and potassium and the incidence of hypertension at the Cimaung Public Health Center, Bandung Regency. There is no relationship between nutritional status, fiber and the incidence of hypertension at the Cimaung Public Health Center, Bandung Regency.